Effects of Overweight and Obesity on Hypertension in Adolescents: A Meta-Analysis - Nurussyifa Afiana Zaen; Didik Tamtomo; Burhannudin Ichsan (Journal of Epidemiology and Public Health, 2023)
Background: Hypertension is currently starting to show a trend in prevalence that continues to increase at a younger age and is a major cause of premature death in the world. In adolescents, hypertension is more common who are overweight or obese. This study aims to examine the effect of overweight and obesity on the incidence of hypertension in adolescents using a meta-analysis.Subjects and Method: Meta-analysis was carried out using the PRISMA flow chart and the PICO model. Population: adolescents aged 10 to 19 years. Intervention: overweight and obesity. Comparison: normoweight. Outcome: hypertension). The databases used are PubMed, Science Direct, Springer Link, and Google Scholar with the keywords (hypertension OR "High Blood Pressure") AND "BMI Status" AND (adolescent OR teenager) AND "cross sectional". There were 9 cross-sectional studies published in 2012-2022 with odds ratio (OR) effect size that met the inclusion criteria. Analysis was performed with RevMan 5.3.Results: A meta-analysis was conducted on 9 articles with a cross-sectional study design originating from China, South Korea, India, Turkey, Tunisia, Lithuania and Poland involving 63,239 adolescents aged 10-19 years. The results of the meta-analysis showed that overweight adolescents were 2.44 times more likely to experience hypertension compared to normal weight adolescents (aOR= 2.44; 95%CI= 1.87 to 3.19; p<0.001), and obese adolescents were more likely to experience hypertension 4.53 times compared with normal weight adolescents (aOR= 4.53; 95% CI= 3.10 to 6.61; p<0.001).Conclusion: Being overweight and obese can increase the risk of developing hypertension in adolescents. Keywords: overweight, obesity, hypertension, adolescents, meta-analysis Correspondence: Nurussyifa Afiana Zaen. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: nurussyifaaz20@gmail.com. Mobile: +6287723131415.